In vitro cytotoxicity of some hemostatic agents used in apicoectomy to human periodontal ligament and bone cells - Panupat Phumpatrakom (2020)
© 2019 Saudi Endodontic Journal | Published by Wolters Kluwer - .Medknow. The aim of this study was to test the cytotoxicity of some hemostatic agents used in periapical surgery to primary human periodontal and bone cells. Materials and Methods: Primary human periodontal ligament and bone cells were divided into five experimental and two control groups. In each of the experimental groups, the cells were cultured in complete media containing various concentrations of different hemostatic agents: epinephrine, aluminum chloride, aluminum sulfate, ferric sulfate, or tranexamic acid. The cytotoxicity was evaluated at 1 min, 5 min, and 24 h. Regular complete medium and sodium hypochlorite were used as positive and negative control groups, respectively. The number of viable cells was investigated using MTT assay. The data were analyzed statistically at the 95% confidence interval. Statistical Analysis Used: The statistical analysis was done using Kruskal-Wallis and multiple comparisons tests. Results: The cytotoxicity of all hemostatic agents was time and concentration dependent. Epinephrine and tranexamic acid showed mild or no toxicity to both human periodontal and bone cells at all-time points. Aluminum chloride, aluminum sulfate, and ferric sulfate were moderately to highly toxic to the cells. No significant difference was found between epinephrine and tranexamic acid (P < 0.05). Conclusions: Epinephrine and tranexamic acid tended to be nontoxic or mildly toxic to periodontal ligament and bone cells. Both of them might be considered as the appropriate hemostatic agents for surgical endodontics.